2020
DOI: 10.1155/2020/9602016
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Profiling of Type 2 Diabetes Mellitus by Bioinformatics Analysis

Abstract: Objective. The aim of this study was to identify the candidate genes in type 2 diabetes mellitus (T2DM) and explore their potential mechanisms. Methods. The gene expression profile GSE26168 was downloaded from the Gene Expression Omnibus (GEO) database. The online tool GEO2R was used to obtain differentially expressed genes (DEGs). Gene Ontology (GO) term enrichment analysis and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis were performed by using Metascape for annotation, visualization, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 46 publications
(42 reference statements)
0
11
0
Order By: Relevance
“…Inflammatory response—the most significant biological process—is documented to be associated with diabetes [ 31 ]. G-protein-coupled receptor signaling pathways are related with the crosstalk with insulin signaling [ 32 ], while chemokines have been found to be associated with or implicated in the pathogenesis of type 1 diabetes [ 30 ]. Type 2 diabetes has broad impact on immune responses [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Inflammatory response—the most significant biological process—is documented to be associated with diabetes [ 31 ]. G-protein-coupled receptor signaling pathways are related with the crosstalk with insulin signaling [ 32 ], while chemokines have been found to be associated with or implicated in the pathogenesis of type 1 diabetes [ 30 ]. Type 2 diabetes has broad impact on immune responses [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…The data indicated that these genes could participate in modulating inflammatory response and β cell dysfunction. In previous bioinformatic analysis, PIK3R1, RAC1, GNG3, GNAI1, CDC42, and ITGB1 have been identified as candidate genes of the pathogenesis of type 2 diabetes [ 33 ]. For instance, epidemiological studies have demonstrated that PIK3R1 exerts a critical role in insulin signal transduction during type 2 diabetes development [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in vivo models of mouse obesity have demonstrated that the absence of JNK1 would improve insulin sensitivity ( 29 ). In addition, studies on Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis of T2D-associated genes have revealed that MAPK signaling pathways are associated with T2D ( 30 , 31 ). An in vivo study using a p38 MAPK inhibitor to treat db/db mice showed that inhibition of the p38 MAPK pathway could reduce blood glucose level and improve the function of β-cells, thus ameliorating the pathogenesis of T2D ( 32 ).…”
Section: Discussionmentioning
confidence: 99%